The Association between Allergies and Hematologic Tumors - A Review - Aleksandra Hrapkowicz; Joanna Szydziak; Kinga Janowska; Olga Szeidl; Dominika Rehan; Julia Wołoszczak; Agnieszka Mioskowska; Daria Dąbkowska (Kazimierz Wielki University, 2024)
Introduction: Dysfunctions of the immune system in allergic diseases and hematological malignancies are the subject of many studies due to the mechanisms that link them. Chronic inflammation created in the immune response in an allergic reaction has been associated with developing neoplastic diseases.  Aim of the study: This review examines the potential correlation between Allergies and Hematologic Tumors: acute lymphoblastic leukemia, childhood leukemias, non-Hodgkin and Hodgkin lymphomas.   Material and methods: An English-language literature review was conducted, analyzing studies from the PubMed database up to October 2024 regarding the correlation between Allergies and Hematologic Tumors. The review was performed using the PubMed database, with 50 works used.  Conclusions: The relationship between allergies and hematological tumors is unclear. According to some studies, this relationship does not exist; some state, however, that allergic diseases show correlations with hematological malignancies. The results of these studies do not provide a clear answer to whether this is a positive or negative relationship. Some studies suggest that allergies reduce the risk of hematological malignancies, while others contradict this, suggesting that allergies may increase the risk of hematological tumors. The results of studies showing an increased risk of hematological malignancies in people suffering from allergies can be due to the hypothesis of antigenic stimulation, which may explain the mechanism of correlation between those diseases. This hypothesis suggests that chronic immune stimulation predisposes to hematologic malignancies such as multiple myeloma, non-Hodgkin's lymphoma (NHL), and leukemia by promoting the development of randomly occurring pro-oncogenic mutations in actively dividing immune cells. Different results on this potential correlation showed that further studies are necessary.